2016
DOI: 10.5860/rusq.55n3.230
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Fresh Look: Reviewing and Classifying Reference Statistics for Data-Driven Decision Making

Abstract: This article describes the results of an extensive review of reference transactions from multiple service points at the University of Utah’s J. Willard Marriott Library. The review enabled us to better understand the types of questions asked at our service points and resulted in a new set of codes for categorizing reference transactions that focus on recording the kinds of expertise needed to answer each question. We describe the differences between our model and other scales for collecting reference questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…From the literature review, we found inspiration for subject categories (LeMire et al, 2016;Lenkart & Yu, 2017;Radford & Connaway, 2013;Ryan, 2008), but we chose to use terminology that would fit into the context of a large Norwegian university library and that our colleagues at the service desks would be familiar with. We decided to use the following categories: Collection and Access, Counselling/Guidance 2 , Citing and Referencing, Loan, Practical questions 3 , IT questions, and Other questions 4 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the literature review, we found inspiration for subject categories (LeMire et al, 2016;Lenkart & Yu, 2017;Radford & Connaway, 2013;Ryan, 2008), but we chose to use terminology that would fit into the context of a large Norwegian university library and that our colleagues at the service desks would be familiar with. We decided to use the following categories: Collection and Access, Counselling/Guidance 2 , Citing and Referencing, Loan, Practical questions 3 , IT questions, and Other questions 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Time dedicated to the transaction is also recognized in the READ scale (Gerlich & Berard, 2007). LeMire et al (2016) chose not to use any of the existing scales because they tended to pre-assign higher value to in-depth, subject-oriented reference questions. The authors believed that, "…even 'simple' question types can give patrons valuable help and can turn into complex information searches" (p. 231).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A hallmark of neoliberalism in library service structures is the commodification of patrons and their data (Mathios,125 2019). Even though varied metrics such as in-house materials usage statistics (Rose-Wise & Irwin, 2016), circulation statistics (Rose-Wiles et al, 2020), and reference transaction statistics (Beirne & Aldridge, 2012;Dubnjakovic, 2012;Empey, 2010;LeMire et al, 2016;Ryan, 2008) continue to be used to gauge the value of libraries, these methods are ill-suited to establish with confidence authentic correlations between student success and the utilization of library resources and services. Thorpe et al (2016) write that "changes in student use of the library, both physically and virtually, mean that gate counts, room use counts, in-house print collection tick marks, and attendance for library instruction sessions are insufficient measures for showing student engagement with the library" (p. 373).…”
Section: Establishing Protocols For the Collection And Management Of Datamentioning
confidence: 99%